2022
DOI: 10.4103/idoj.idoj_306_21
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Inflammatory Cytokine mRNA Expression of Tumour Necrosis Factor- Alpha (TNF α), Interleukin 17A (IL 17A) and Interleukin 6 (IL 6) in Indian Patients with Psoriasis

Abstract: Background: Psoriasis, a chronic, immune-mediated skin disorder, has systemic manifestations as well as an ample negative impact on the quality of life (QOL) of the patient. An abnormal proliferation of keratinocyte and dermal infiltration by immune cells is a characteristic feature. It involves components of both innate and adaptive immunity, and the interaction of T cells with macrophages. Keratinocytes and dendritic cells are mediated by the secreted cytokines. This study was taken up to look i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Our research also indicated a potential role of rs3093662 ( TNF ) in PsO etiology as we noticed that G allele carriers had a 2.175 times higher risk of developing PsO ( p = 2.40 × 10 −6 ). Similarly to other studies, we observed a significant increase in mRNA TNF in PsO [ 26 , 27 ]. Therefore, it seems likely that the involvement of genetic factors in TNF function may indirectly contribute to the Treg-mediated response in PsO, but this requires further research.…”
Section: Discussionsupporting
confidence: 91%
“…Our research also indicated a potential role of rs3093662 ( TNF ) in PsO etiology as we noticed that G allele carriers had a 2.175 times higher risk of developing PsO ( p = 2.40 × 10 −6 ). Similarly to other studies, we observed a significant increase in mRNA TNF in PsO [ 26 , 27 ]. Therefore, it seems likely that the involvement of genetic factors in TNF function may indirectly contribute to the Treg-mediated response in PsO, but this requires further research.…”
Section: Discussionsupporting
confidence: 91%
“…The variations of cytokine levels across studies may be due to different study designs, different genetic backgrounds, or may reflect the influence of concomitant diseases. A recent study of psoriasis patients without any associated comorbidities using highly sensitive methods of detecting cytokine mRNA provides evidence of increased mRNA expression of IL-17A in blood samples of patients compared to that in normal subjects 57 thus emphasizing the major role of IL-17 in psoriasis.…”
Section: Discussionmentioning
confidence: 99%